PERLINDUNGAN SUMBER DAYA PERIKANAN UNTUK MENJAMIN TERWUJUDNYA PEMBANGUNAN PERIKANAN BERKELANJUTAN (Studi Terhadap Pelaksanaan Perlindungan Lobster, Kepiting dan Rajungan Berdasarkan Peraturan Menteri Kelautan dan Perikanan Nomor 1/MEN-KP/2015 tentang Penangkapan Lobster, Kepiting dan Rajungan) Di Kabupaten Jepara - Ahmad Chotib; Djauhari Djauhari (Jurnal Hukum Khaira Ummah, 2018)
The Research is the legal research that a descriptive analysis, using the approach empirical juridical, namely to identify and conceptualize law basing on real experiences which is then used to analyze the data and make inferences about the problems studied so that the data needed form-spread distribution of information that does not need to be quantified, with the method of data collection and documentation in the form of literature studies, observations, interviews, using primary and secondary data sources in the form of legal materials. Legal materials obtained from the literature as well as field observations were then analyzed using qualitative descriptive method. Then from this study can dirmuskan several problems: 1) how the implementation of the special protection of fishery resources lobster, crab and crab Jepara based on the Minister of Marine and Fisheries No. 1 / MEN-KP / 2015 ?; 2) What are the barriers and solutions made in the implementation of the special protection of fishery resources Lobster, Crab and Rajungan Jepara?.Based on the survey results revealed that for the protection of fishery resources specifically lobster, crab and crab in the context of preservation there are some attempts to do is to immediately issue implementing regulation on the issuance of Ministry of Marine Affairs and Fisheries No. 1 / MEN-KP / 2015, maximizing socialization of the relevant agencies Regulation of the Minister of Marine and Fisheries No. 1 / MEN-KP / 2015 so it does not happen again the practice of catching lobsters, crabs and crabs in the wild. However in practice there are obstacles in between the absence of instructions and technical implementation of the Regulation of the Minister of Marine and Fisheries No. 1 / MEN-KP / 2015 itself, lack of human resources fishing communities with respect to the pattern of empowerment aquaculture lobster, crab and crab, lack of awareness community in keeping with existing regulations, and weak supervision and therefore contributes to arrests in various district of Jepara that tends arbitrarily without considering the sustainability aspect of course is worrying in terms of quantity which will become extinct.Keywords: resources, fisheries, conservation